ANALISIS PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PRAKTIK PENGHINDARAN PAJAK - Martha Carolina (Pusat Kajian Anggaran, 2020)
This study uses agency theory that explains the difference of interests (agency problems) between principals and agents. To solve these difference of interests, it uses aggressive tax avoidance in order to optimize both interests. This study uses observation of secondary data obtained from the audited financial statements of manufacturing companies.The results showed that this study had passed classic assumption test. The F test shows that the independent variables jointly influence the dependent variable with significant value of 0,000. The t test results showed profitability (ROA) and leverage (DER) with each a significant value of 0,000; 0,870. Finally, the conclusion of this study shows that ROA variable (X1) affects tax avoidance (Y), ROA has a negative effect on tax avoidance. whereas DER variable (X2) has no effect on tax avoidance (Y).